FOREIGN EXPERIENCE IN PROVIDING TOURISM SERVICES IN TRANSPORT - Tuychiev Anvarjon Muxtorjonovich (Modern American Journals, 2025)
This study examines foreign experience in providing tourism services within transport systems, focusing on the economic and organizational integration of transport and tourism. It analyzes international practices in air, rail, road, and maritime transport that enhance accessibility, service quality, and tourist satisfaction. The research highlights the role of strategic planning, public–private partnerships, and digital technologies in improving the efficiency and competitiveness of transport-based tourism services. The findings demonstrate that effective transport–tourism integration contributes to increased tourist flows and sustainable economic development.
Keywords: Transport services, tourism infrastructure, international experience, transport economics, service quality, public–private partnership, digital transport solutions.